1996
DOI: 10.2337/diab.45.4.471
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Induces Antioxidant Enzymes in Human Endothelial Cells in Culture: Evidence Linking Hyperglycemia and Oxidative Stress

Abstract: It has been suggested that oxidative stress may play an important role in the pathogenesis of diabetic complications. Hyperglycemia may cause increased production of free radicals, and evidence supports a prominent role for these reactive molecules as mediators of endothelial cell dysfunction in diabetes. It has been demonstrated that active oxygen species induce antioxidant enzyme expression in some tissues, and this phenomenon is considered proof of an existing oxygen-dependent toxicity. In this study, human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(103 citation statements)
references
References 0 publications
8
94
1
Order By: Relevance
“…Diabetes is a condition in which the hyperglycemia and oxidation of glucose produces large amounts of free radicals, thereby leading to increased activity and expression of antioxidant enzymes [21]. Insulin resistance is also related to the production of intracellular free radicals, and strategies to downregulate intracellular reactive oxygen species (ROS) have been identified as a potential treatment for diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a condition in which the hyperglycemia and oxidation of glucose produces large amounts of free radicals, thereby leading to increased activity and expression of antioxidant enzymes [21]. Insulin resistance is also related to the production of intracellular free radicals, and strategies to downregulate intracellular reactive oxygen species (ROS) have been identified as a potential treatment for diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that high glucose induces an increase in antioxidant enzyme levels in human endothelial cells;27 however, it was speculated in that study that hyperglycemia may cause increased production of free radicals, and evidence supports a prominent role for these reactive molecules as mediators of endothelial cell dysfunction in diabetes. Those findings appear to be contradictory, so further investigation is necessary to fully elucidate the mechanism for less progression of NS in diabetic patients.…”
Section: Discussionmentioning
confidence: 88%
“…In experimental cell models, exposure to elevated glucose levels foster oxidant stress mechanisms that lead to cell injury in cardiomyocytes (35, 39, 102), neurons (55, 63, 69, 103, 104), and endothelial cells (62, 6568, 105). Elevations in serum glucose also can increase antioxidant enzyme levels in human endothelial cells, suggesting that some cells can attempt a reparative process during oxidative stress exposure (106). In clinical studies, patients with Type 2 DM display serum markers of oxidative stress with ischemia-modified albumin (107).…”
Section: Dm Involvement Of Multiple Organ Systems and Oxidative mentioning
confidence: 99%